2007
DOI: 10.1073/pnas.0607196104
|View full text |Cite
|
Sign up to set email alerts
|

The SCL transcriptional network and BMP signaling pathway interact to regulate RUNX1 activity

Abstract: Hematopoietic stem cell (HSC) development is regulated by several signaling pathways and a number of key transcription factors, which include Scl/Tal1, Runx1, and members of the Smad family. However, it remains unclear how these various determinants interact. Using a genome-wide computational screen based on the well characterized Scl ؉19 HSC enhancer, we have identified a related Smad6 enhancer that also targets expression to blood and endothelial cells in transgenic mice. Smad6, Bmp4, and Runx1 transcripts a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
104
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 111 publications
(112 citation statements)
references
References 40 publications
7
104
0
1
Order By: Relevance
“…7D). Given that RUNX1 activates IL2 transcription [8] and that pRUNX1 is increased by the activation of RUNX1 [16], these results suggested that BMP signalling regulated IL-2 transcription via activating RUNX1 in T cells.…”
Section: A Complex Effect Of Dm On Il-2 Production Of T Cellsmentioning
confidence: 90%
See 3 more Smart Citations
“…7D). Given that RUNX1 activates IL2 transcription [8] and that pRUNX1 is increased by the activation of RUNX1 [16], these results suggested that BMP signalling regulated IL-2 transcription via activating RUNX1 in T cells.…”
Section: A Complex Effect Of Dm On Il-2 Production Of T Cellsmentioning
confidence: 90%
“…First, IL-2 production is the crucial mechanism of T-cell activation. Second, IL2 transcription is known to be regulated by several key transcription factors, one of which is AML1/ RUNX1, a well-established downstream target of BMP signalling in hematopoietic lineage cells [8,14,15].…”
Section: A Complex Effect Of Dm On Il-2 Production Of T Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…At a posttranscriptional stage, Runx1 levels can be controlled by miR-27a in a feed-back loop, which involves the positive regulation of miR-27a by Runx1 (4). At a posttranslational stage, we have reported previously that Runx1 levels are controlled by Smad6/Smurf1-mediated proteasome degradation (28), but how this control mechanism is integrated within the hematopoietic transcriptional network is not clear. Smad6 is an inhibitor of Bmp4 signaling (14), a key driver of HSC development (18).…”
mentioning
confidence: 99%